Perioperative active warming strategies in children: a protocol for a multicentre, prospective, randomized controlled trial - Qiao, Lanxin; Wang, Yaxin; Liang, Yi; Xia, Tian; Li, Ling; Xiong, Wei; Liu, Bin; Feng, Yifan; Liu, Yan; Jin, Xu; Zhang, Jianmin (Frontiers in Pediatrics, 2023)
Introduction Inadvertent perioperative hypothermia (IPH) refers to a core body temperature lower than 36.0 °C, which can contribute to many adverse events. The special physiological characteristics in children further increase the incidence of IPH. Therefore, it is very important to perform effective perioperative warming measures for children. Traditional passive warming measures with additional layers have limited thermal insulation effects. Active warming measures might be the better choice, and most measures have achieved good effects in adults. This study combines a variety of active warming measures to propose perioperative active warming strategies and aims to verify the feasibility and thermal insulation effects of perioperative active warming strategies in children. Methods This study is a multicentre, prospective, randomized controlled trial. From August 2022 to July 2024, 400 paediatric patients undergoing elective surgery will be recruited in four centres and randomly divided into the active warming strategies group and control group at a ratio of 1:1. The primary outcome is the perioperative cumulative hypothermia effect value (Σ ΔTi × Δti, i = 1…, n). Multiple complications covering the anaesthesia recovery period and postoperative hospitalization will be considered as secondary outcomes to comprehensively analyse the prognosis. Trial registration ClinicalTrials.gov identifier: ChiCTR2200062168. Registered on July 26th, 2022. Registered with the name of “Perioperative Active Warming Strategies in Children: A multicenter, prospective, randomized controlled trial”. URL:http://www.chictr.org.cn/showproj.aspx?proj=172778.